``Desarrollo y caracterización de recubrimientos comestibles a partir de residuos de la cadena de beneficio de cacao (theobroma cacao l.) Mucílago de cacao ccn-51`` - Gaón Ortiz, Gabriela Stefania (2022)
Currently, the cocoa industry generates a lot of waste and residues which have been a focus of attention for several researchers worldwide, since these residues are often not used or are not disposed of properly and are deposited on the ground. Today the main drawback they present is the lack of environmental awareness for their management and the little capacity to give it an appropriate final destination. Among the residues of the cocoa industry,